Antimicrobial peptide S100A12 (calgranulin C) inhibits growth, biofilm formation, pyoverdine secretion and suppresses type VI secretion system in Pseudomonas aeruginosa. (August 2022) - Mishra, Priyasha; Ch, Sanjay; Hong, Seok Jong; Biswas, Swati; Roy, Sanhita
Abstract: Pseudomonas aeruginosa is an opportunistic pathogen and is the major cause of corneal infections in India and worldwide. The increase in antimicrobial resistance among Pseudomonas has prompted rise in significant research to develop alternative therapeutics. Antimicrobial peptides (AMPs) are considered as potent alternatives to combat bacterial infections. In this study, we investigated the role of S100A12, a host defense peptide, against PAO1 and an ocular clinical isolate. Increased expression of S100A12 was observed in corneal tissues obtained from Pseudomonas keratitis patients by immunohistochemistry. S100A12 significantly inhibited growth of Pseudomonas in vitro as determined from colony forming units. Furthermore, recombinant S100A12 reduced the corneal opacity and the bacterial load in a mouse model of Pseudomonas keratitis. Transcriptome changes in PAO1 in response to S100A12 was investigated using RNA sequencing. The pathway analysis of transcriptome data revealed that S100A12 inhibits expression of genes involved in pyoverdine synthesis and biofilm formation. It also impedes several important pathways like redox, pyocyanin synthesis and type 6 secretion system (T6SS). The transcriptome data was further validated by checking the expression of several affected genes by quantitative PCR. Our study sheds light on how S100A12 impacts Pseudomonas and that it might have the potential to be used as therapeutic intervention in addition to antibiotics to combat infection in future. Highlights: Increased protein expression of S100A12 in patients with Pseudomonas keratitis. S100A12 inhibits growth of P . aeruginosa in vitro. Transcriptome data show reduced expression of genes for biofilm formation and pyoverdine synthesis in PAO1 by S100A12. Topical application of S100A12 promotes protection during P. aeruginosa infection in a murine model of keratitis.